Attitudes towards carbon taxation in the EU: messenger effects vs. content effects - Alessio Levis; E. Keith Smith; Silvia Pianta (Journal of Public Policy, 2026)
Abstract This paper investigates how European Union institutional sources influence public support for carbon taxes through messenger effects. Our framework predicts that support decreases with higher tax rates, an effect moderated by respondents’ associations with the source, namely trust, euroscepticism, and national identity. We run a pre-registered survey-embedded vignette experiment in Germany and Poland ( N = 3192), in which respondents evaluate carbon tax policies for car, aviation, and heating fuels. Proposals vary in tax rate (10%, 50%, 100%) and supporting source (European Commission, national government, foreign government). We find that higher tax rates decrease support and that source-specific effects are driven by trust, but not by national identity or euroscepticism, which instead structure baseline support across all actors. Moreover, positive messenger cues do not moderate the negative effect of costs. These findings show that institutional attitudes matter for carbon tax support, but that policy costs remain central.